THE EFFECT OF FIRM’S CHARACTERISTIC AND CORPORATE GOVERNANCE TO SUSTAINABILITY REPORT DISCLOSURE - Lucia, Lucia; Panggabean, Rosinta Ria (SEEIJ (Social Economics and Ecology International Journal), 2018)
The purpose of this study was to analyze the effect of company’s characteristic which are profitability (ROA), leverage (DER), liquidity (CR), company size (SIZE), and corporate governance proxied by board of directors and audit committee (KA) to disclosure of sustainability reports (SR). The study had 105 samples of manufacturing companies listed in Indonesia StockExchange and 262 manufacturing companies listed on Malaysia Exchange in year 2013-2015. Data analysis using regression logistic method with E-views version 9. Hypothesis testing results show that the partial results of hypothesis testing variable DER, CR, and Directors do not have significant effect on internet financial reporting, but ROA and SIZE have significant influence on sustainability report disclosure (SR) of manufacturing companies listed in IDX and Bursa Malaysia.